Regulation of glucose-6-phosphate dehydrogenase under salt-stress condition in Aspergillus sydowii. - T. Parekh; H. S. Chhatpar (Fungal Genetics Reports, 1989)
Physiological responses of organisms to particular stresses are well understood in only a few cases (Bachofen, R. 1986 Experientia 42:1179-1182)